Pengembangan Multimedia Interaktif Biologi Berbasis Savi (Somatic, Auditory, Visual, Intelectual) Pada Materi Monera Kelas X IPA - Jum’ah, Syamsul; Ekaningtias, Maya (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
The objectives of this study were: (1) to produce of interactive multimedia learning media based on SAVI (Somatic, Auditory, Visual, Intelectual) for teaching materials of monera, and (2) to determine the advisability of the learning media. The learning media developed using the ADDIE model. But, this study only used three steps, which were define, design, develop steps. The result of validation scores showed that the interactive multimedia learning media based on SAVI (Somatic, Auditory, Visual, Intelectual) of monera materials was very advisible to be used.